IMFIs Strategy to Survive in the Covid-19 Outbreak and Government Respond Analysis : An Empirical Study from Pekanbaru, Indonesia - Trianto, Budi; Chandra, Ade; Munthe, Marabona (BISNIS, 2020)
The Covid-19 outbreak had a broad impact on the economy and also on the business sector. One of the business sectors affected by Covid-19 is Islamic Microfinance Institutions (IMFIs). This study aims to explore the strategies taken by IMFIs during the Covid-19 pandemic and to explore the government's policy response toward the Covid-19 disaster. This research was conducted in Pekanbaru using a qualitative approach and using primary data and secondary data in conducting the analysis. Primary data were taken directly from research respondents through in-depth interviews with IMFIs managers. Meanwhile, secondary data were obtained from the government and other sources. The results of this study indicate that the approach strategy taken by IMFIs in responding to the Covid-19 outbreak is a Generic Strategy Approach which consists of cost leadership, focus cost, differentiation and cost differentiation. Meanwhile, the government policy responded taken to save IMFIs from the Covid-19 storm through profit margin subsidies. Unfortunately, the implementation in the field has experienced many obstacles that have greatly disturbed the economic recovery program launched by the government. The results of this study have implications for IMFIs that in order to survive the Covid-19 pandemic, IMFIs must adapt an appropriate strategies. In addition, this study also provides recommendations for the government to simplify the procedure for disbursing profit margin subsidies for IMFIs so that it is hoped that the policy will truly benefit IMFIs and business actors.